If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-4x + 11) = 0 Reorder the terms: (11 + -4x) = 0 Remove parenthesis around (11 + -4x) 11 + -4x = 0 Solving 11 + -4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -4x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -4x = 0 + -11 -4x = 0 + -11 Combine like terms: 0 + -11 = -11 -4x = -11 Divide each side by '-4'. x = 2.75 Simplifying x = 2.75
| 3(2a+b-3c)= | | (x+4)+(3x-7)= | | k/2=-20 | | (2x+10)2=(3x-55)2 | | -1+3.3h=-16 | | (8x)0(8x)= | | 50+6m= | | 9+x=-8x-18 | | X=50-46 | | (2x^3-2/7)^3 | | 3y+3+2y+6=10y-31 | | -9+3n=-63 | | g(n)=25-49(n-1) | | k/3=-16 | | ((2x^3-2/7))^3 | | -32=-17+x | | 99=9y | | -0.6u-9=-5 | | 2(3z-1)-2(4-2Z)=8 | | 13x-7=12x-12+x+5 | | -3/2y=22 | | 75-9n= | | p/14=1 | | -20=k-19 | | 10x-16=8x+7 | | -54=9h | | 4b+2=9b-23 | | 0.28y+8=11 | | 3(6x-5)=18x+15x | | b/17=-13 | | 4(x-30)+5x=-48 | | x+(1+x)+(2+x)=228 |